2017
DOI: 10.17140/prrmoj-4-137
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Pulmonary and Extra Pulmonary Tuberculosis: How Best is CBNAAT when Compared to Conventional Methods of TB Detection?

Abstract: CitationKandi S, Reddy V, Nagaraja SB. Diagnosis of pulmonary and extra pulmonary tuberculosis: How best is CBNAAT when compared to conventional methods of TB detection? Pulm Res Respir Med Open J. 2017; 4(2): 38-41. doi: 10.17140/ PRRMOJ-4-137 ABSTRACT Background: Globally, India is a home for more than 25% of global Tuberculosis (TB) burden. The sensitivity of smear microscopy and its inability to detect drug resistance limits its impact on TB control. We compared the cartridge-based nucleic acid amplificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…For extra-pulmonary samples ,the sensitivity and specificity of CBNAAT samples were 85.7% and 93.5% respectively while that for smear negative were 60.7% and 100% respectively. 16 CBNAAT is a useful surrogate test for screening for MDR-TB as past studies on drug resistance have shown that rifampicin resistance seldom occurs alone and around 90% of rifampicin resistant patients are diagnosed to have MDR -TB. 12 The specificity of CBNAAT in detecting rifampicin resistance is very high (98%), and increasing evidence has shown that the infrequent occurrence of so-called false-positive results may be linked to the detection by Xpert MTB/RIF of strains that are truly resistant to rifampicin, but which are not detected by the phenotypic culture-based DST, the present reference standard.…”
Section: Resultsmentioning
confidence: 99%
“…For extra-pulmonary samples ,the sensitivity and specificity of CBNAAT samples were 85.7% and 93.5% respectively while that for smear negative were 60.7% and 100% respectively. 16 CBNAAT is a useful surrogate test for screening for MDR-TB as past studies on drug resistance have shown that rifampicin resistance seldom occurs alone and around 90% of rifampicin resistant patients are diagnosed to have MDR -TB. 12 The specificity of CBNAAT in detecting rifampicin resistance is very high (98%), and increasing evidence has shown that the infrequent occurrence of so-called false-positive results may be linked to the detection by Xpert MTB/RIF of strains that are truly resistant to rifampicin, but which are not detected by the phenotypic culture-based DST, the present reference standard.…”
Section: Resultsmentioning
confidence: 99%
“…CB-NAAT as a rapid diagnostic test, should be routinely used in public and private health sectors efficiently for the detection of a case of tuberculosis. 11 In cases of extrapulmonary tuberculosis, nucleic acid amplification tests appears to be an attractive modality with a high specificity, positive predictive value and highly variable sensitivity. 12…”
Section: Discussionmentioning
confidence: 99%
“…In a study done Kandi et al the sensitivity of CBNAAT for pulmonary samples was 79% when compared to sputum smear which was 42%. [6][7][8] Cite this article as: Kumar P, Bhardwaj P. Diagnosis of pulmonary tuberculosis with cartridge based nucleic acid amplification test and light emitting diode fluorescent microscopy: a comparative study. Int J Adv Med 2019;6:1580-3.…”
Section: Discussionmentioning
confidence: 99%